Effectiveness of tacrolimus therapy in refractory ulcerative colitis compared to infliximab with propensity score matching - Takeo Yoshihara; Takahiro Amano; Shinichiro Shinzaki; Yuri Tsujii; Akiko Asakura; Taku Tashiro; Mizuki Tani; Yuriko Otake-Kasamoto; Takuya Yamada; Yuko Sakakibara; Naoto Osugi; Shuji Ishii; et al. (Scientific Reports)
Abstract There is insufficient evidence comparing the outcomes of tacrolimus-based remission induction therapy with infliximab in refractory ulcerative colitis (UC) and evidence regarding optimal strategies after tacrolimus-based remission induction therapy. We conducted a multi-institutional retrospective study of patients with UC treated with tacrolimus or infliximab between January 2010 and March 2019. The proportion of clinical remission at week 8 and cumulative colectomy-free rate were examined using propensity score matching analysis. The predictors for colectomy after tacrolimus induction were also investigated. Ninety patients in the tacrolimus group and 151 in the infliximab group were enrolled. The proportion of patients in clinical remission at week 8 was 65.2% in the matched tacrolimus group and 37.3% in the matched infliximab group (P = 0.0016), and the long-term colectomy-free rate was lower in the matched tacrolimus group than in the matched infliximab group (P = 0.0003). After clinical remission with tacrolimus, a serum albumin level of ≤ 3.5 g/dL at week 8 was extracted as a factor predicting colectomy (area under the curve: 0.94). Tacrolimus showed a higher remission induction effect for UC compared to infliximab. However, a high rate of colectomy after transition to maintenance treatment was found to be a concern for tacrolimus therapy.